A geração sênior da sociedade contemporânea brasileira : os desafios na construção da identidade no século XXI - Rodrigues, Flavia Luciana dos Santos Souza (2016)
This study aims to identify and explore the key behavioral habits, lifestyles and construction of a new personal image of individuals 60 years or more, pictured in this dissertation, as 'senior generation'. By allowing themselves to track changes through fashion in contemporary society, in the face of rising expectations and quality of life, they see themselves as important transmitters of new meanings, using them as tools of socialization, identity and belonging. Thus, the senior is revolutionizing the concept of aging in contemporary society, rediscovering values conducive to personal fulfillment, where the senior learn to build his story. Realizing the active longevity as feasible, the prospects for the future become, through the challenge of time and aging stereotypes, use the technologies as ways of interaction and integration. Aesthetic procedures become increasingly more allied in the search for disguise timelines, and effect, soften the perception of aging, holding a significant role in consumer products and services. The senior generation is active and protagonist of the story itself as it aims for changes in appearance, demands for products that bring beauty, well-being and elegance, however, they think the market is incompatible with their expectations. This research is based on survey of bibliographic information. The methodology involves a qualitative analysis and concepts, addressing the design of fashion and personal image of a generation of bold and creative people looking for recognition in the society in which they live.